MANAGEMENT OF ENDOCRINE DISEASE: Bone disorders associated with acromegaly: mechanisms and treatment. Issue 2 (August 2019) - Mazziotti, Gherardo; Lania, Andrea G A; Canalis, Ernesto
Abstract : Growth hormone (GH) and insulin-like growth factor-I (IGF-I) exert physiological actions on the skeleton throughout life, by stimulating longitudinal bone growth in children, the acquisition of bone mass during adolescence and the maintenance of skeletal architecture in adults. When GH and IGF-I are secreted in excess, bone remodeling is enhanced leading to deterioration of bone microstructure and impairment of bone strength. Indeed, acromegaly causes skeletal fragility, and vertebral fractures are reported in a remarkable number of subjects exposed to GH and IGF-I excess. The management of skeletal fragility in acromegaly is a challenge, since the awareness of this complication is low, the prediction of fracture risk is difficult to ascertain, the risk of fractures remains after the control of acromegaly and the effectiveness of bone-active drugs is unknown. This review is an update on bone disorders associated with acromegaly and provides a perspective of possible therapeutic approaches based on emerging pathophysiological and clinical information.